Communication Accommodation Analysis of Mobile Legend Online Game Player Group at Telu Esports - Putri Shalsa Bil Balqis; Ratih Hasanah Sudradjat (Jurnal Indonesia Sosial Teknologi, 2024)
Communication accommodation is by definition a form of a person adapting himself or in other words the adaptation made to the person he is speaking to. This research will discuss the analysis of group communication accommodation for mobile legend online game players on Tel-u Alpha. This research aims to determine the group communication accommodation that occurs among mobile legend online game players on Tel-u Alpha. This research uses qualitative methods by collecting data through interviews with focus group discussions conducted with Tel-u Alpha. In this research, Giles uses CAT theory or Communication Accommodation Theory. The research results showed that there were adjustments made by each member of the Tel-u Alpha team because adjusting their way of communicating, would make it easier for the team to achieve common goals. This can happen because communication accommodation aims to equalize perceptions to reduce conflict that will occur in a group.